Erythroderma patient with chronic kidney disease treated with systemic corticosteroids - Anggraini, Ita; Dermawan, Yuwandita TP (Journal of Pakistan Association of Dermatologists, 2024)
Erythroderma is a rare but emergency case because it is a potentially life-threatening condition. It is described as generalized erythema and skin scaling, involving greater than 90% of body surface area. It can be caused by several etiologies, which the most common cause is psoriasis. The pathogenesis depends on the underlying cause. Establishing the definitive diagnosis is still challenging since the histopathology examination is gold standard for erythroderma. But not all healthcare facilities have this examination. Some of them use clinical approach to diagnose. Moreover, erythroderma patients should have comprehensive management, including nutritional assessment, correction of fluid and electrolytes imbalances, treatment to secondary infections, topical therapy, and systemic agents. Targeted therapy can be used after the underlying cause is established, but it is still considered because of cost-effectiveness and the availability. As an alternative, systemic corticosteroids could be given as one of the treatments, although it is still debated for the side effects. We described a case of erythroderma in a 56-year-old male patient with chronic kidney disease. The patient was diagnosed with his medical history, physical examination and laboratory examination. The management of this patient is comprehensive including topical and systemic agents. Patient’s clinical improvement after given topical and systemic corticosteroids.